Rapamycin Corrects T Regulatory Cell Depletion and Improves Embryo Implantation and Live Birth Rates in a Murine Model. (December 2019) - Royster, Greene Donald; Harris, Justine C.; Nelson, Amanda; Castro, Yessenia; Weitzel, R. Patrick; Tisdale, John; Heitmann, Ryan J.; DeCherney, Alan H.; Wolff, Erin F.
There are few treatments for patients with recurrent pregnancy loss (RPL) or recurrent implantation failure (RIF). Women with RPL and unexplained infertility have lower T regulatory cell (Treg ) expression when compared to fertile controls. A murine model has been developed with depletion of regulatory T cells (DEREG) after administration of diphtheria toxin (DT), resulting in smaller litter sizes, secondary to embryo implantation failure. Numerous murine studies have shown that adoptive transfer of CD4 + CD25 + FoxP3 + Tregs from donors improves litter sizes in DEREG mice with depleted Tregs . Our hypothesis is that DEREG mice treated with a single dose of DT will deplete Tregs and subsequently decrease litter sizes and that treatment with rapamycin (sirolimus; Pfizer) during the time of embryo implantation will increase Tregs and restore litter sizes nearly back to normal levels. Syngeneic mating of DEREG mice after depletion of Tregs resulted in smaller litter sizes and this defect was reversed when these DEREG mice were treated with rapamycin at the time of embryo implantation. The importance of Tregs at the time of embryo implantation has been well established and immunotherapy treatments, such as rapamycin (mammalian target of rapamycin inhibitor), may prove to be an effective treatment for patients with RPL, RIF, or unexplained infertility with low Treg .